Apocalyptic motifs and images in media texts on Brexit and Ukrainian elections - Krapivnyk, Ganna (Przegląd Wschodnioeuropejski, 2020)
The paper provides the linguistic analysis of verbalising apocalyptic motifs and images in the media texts, devoted to the topical processes of Brexit and Ukrainian elections. It was confirmed that these motifs and images serve as a tool for influencing the recipients and noted that the consideration of the linguistic realization of images and motifs in the texts of media resources refers to the rapidly developing field of media linguistics. The word families, enriching Ukrainian and English with the neologisms related to the above extra-linguistic processes were singled out. The semantic fields of the considered images and motifs were described. Suggestions for further research were outlined.